The Role of Book Series “Duniyazad” in the promotion of Urdu Literature - Aslam, Muhammad; Ali, Liaqat (sourcecoder, 2022)
Asif Farrukhi was an eminent writer of fiction, literary critic, translator, poet and travel writer on the same time. He enriched Urdu literature more then most of his time and age. He was the editor of “Duniyazad” Magazine. As editor, he welcomed and promoted new writers. This magazine made an excellent selection of Urdu literature. It also includes Urdu translations of literary works in other languages. It also provided a platform for writers and poets to emerge. It is a unique kind of magazine. The theme for each issue is chosen and compiled accordingly. It published traditionlist modernist as well as progressive writers. It is the asset and spokesman of the nation. It is a source of domestic and foreign literary and scholarly resources, which it reveals by reading. This research article will prove to be the best reflection of the worldly mood of magazine “Duniyazad. It will reveal the specific themes of this magazine, the domestic and foreign literature which published in it